Effect of RE3+ on Structural Evolution of Rare-Earth Carbonates Synthesized by Facile Hydrothermal Treatment. (14th March 2019) - Spiridigliozzi, Luca; Accardo, Grazia; Frattini, Domenico; Marocco, Antonello; Esposito, Serena; Freyria, Francesca S.; Pansini, Michele; Dell'Agli, Gianfranco
Abstract : In this work, nanoparticles of cerium hydroxycarbonates were synthesized by a facile hydrothermal treatment at 120°C with ammonium carbonate as the precipitating/mineralizer agent in diluted solution. The as-formed amorphous coprecipitate undergoes several morphological and structural modifications as a function of the duration of the hydrothermal treatment, leading after 8 h to the formation of monosized nanoparticles of hexagonal CeCO3 OH. A similar behavior has been found when neodymium-based precursors are used as well, whereas the same treatment produces very different results by using different lanthanides-based precursors in terms of formed phases and morphologies, thus leading to the formation of pure tengerite-type structure phases, biphasic systems (tengerite type and hexagonal), or even entirely amorphous systems. Furthermore, the hydrothermal transformation is influenced by the redox behavior of the rare-earth cation (i.e., cerium) too, eventually resulting in the formation of fluorite-like structures. Therefore, a specific pathway of Ce(III) precursor transformations during hydrothermal treatment is proposed in this paper. Definitely, our results show that ammonium carbonate can be used as the precipitating/mineralizer agent to obtain cerium, doped-cerium, and neodymium hydroxycarbonates, which show excellent morphologies (i.e., characterized by spherical, nanosized particles with monomodal size distribution). Therefore, they can be used as optimal precursors for oxide powders. Conversely, when tengerite-type carbonate precursors are formed, their morphology is characterized by large and acicular particles.